2011
DOI: 10.4103/1817-1737.82440
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, insulin resistance, fibrinogen, homocysteine, leptin, and C-reactive protein in obese patients with obstructive sleep apnea syndrome

Abstract: OBJECTIVE:The prevalence of obstructive sleep apnea syndrome (OSAS) and metabolic syndrome is increasing worldwide, in part linked to epidemic of obesity. The purposes of this study were to establish the rate of metabolic syndrome and to compare fibrinogen, homocysteine, high-sensitivity C-reactive protein (hsCRP), leptin levels, and homeostasis model assessment insulin resistance (HOMA-IR) in the obese patients with and without OSAS.METHODS:The study population included 36 consecutive obese patients with OSAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 42 publications
3
63
0
4
Order By: Relevance
“…Our findings were also consistent with previously published work which shows an association between SDB and conditions such as diabetes [17] and atrial fibrillation [18,19].…”
Section: Cardiovascular Morbiditysupporting
confidence: 83%
“…Our findings were also consistent with previously published work which shows an association between SDB and conditions such as diabetes [17] and atrial fibrillation [18,19].…”
Section: Cardiovascular Morbiditysupporting
confidence: 83%
“…Both OSAHS and Hcy are considered as independent risk factors for cardiovascular disease. [11] Thakre et al [12] have found that the level of Hcy in OSAHS people was significantly higher than that in non-OSAHS people, Sales et al [13] also came to similar results in their research. Animal models have confirmed that the level of Hcy in OSAHS rats is higher than that in non-OSAHS rats; hypoxic changes in OSAHS rats may result from the fact that increased level of Hcy enhances inflammatory responses in the body and leads to the occurrence of AS in cerebral arteries.…”
Section: Discussionsupporting
confidence: 69%
“…In the study of OSAHS and metabolic syndrome, Basoglu et al [11] have found that the level of Hs-CRP in OSAHS group was higher than that in control group, and OSAHS may have a causal relationship with metabolic syndrome. This study showed that OSAHS could promote the increase of Hs-CRP level in patients with cardiovascular diseases such as hypertension and type 2 diabetes, with the severity of AS increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, until 2 years ago, it was unclear whether metabolic syndrome could be reversed by treatment of OSA with continuous positive airway pressure (CPAP). Studies were uncontrolled, small in size and confl icting in their results.…”
mentioning
confidence: 99%